Persepsi Pegawai tentang Budaya Organisasi di Kantor Badan Pertanahan Nasional Kabupaten Pesisir Selatan - Atika Yondria Fatmi; Hadiyanto Hadiyanto (Journal of Educational Administration and Leadership, 2022)
This study aims to find out employee’s perceptions about organizational culture at Kantor Badan Pertanahan Nasional Kabupaten Pesisir Selatan in terms of norms, aggressiveness, team orientation, result orientation, and behavior. This is descriptive research. The population of the study was the employees of Kantor Badan Pertanahan Nasional Kabupaten Pesisir Selatan, amounting to 45 people the sample was taken using the Stratified Proportional Random Sampling technique, with a total of 35 people. Collecting data in this study using a questionnaire in the form of a Likert scale. The results of data analysis show that employees' perceptions of organizational culture at Kantor Badan Pertanahan Nasional Kabupaten Pesisir Selatan can be seen from the following result: (1) norms in organizational culture are good with an average score of 4.2, (2) aggressiveness in organizational culture is good with an average score of 4.1, (3) team orientation in organizational culture is good with an average score of 4.2, (4) results orientation in organizational culture is good with an average score of 4.1 , (5) behavior in organizational culture is good with an average score of 4.2. Overall, it can be concluded that employees' perceptions of organizational culture at Kantor Badan Pertanahan Nasional Kabupaten Pesisir Selatan are good with an average score of 4.16. For this reason, it is recommended that leaders are expected to be able to provide examples, guidance, motivation and explore employee creative ideas. Employees are expected to be able to comply with and guide the norms, participate actively, establish good teamwork, innovate and dare to take risks for the progress of the organization.